A location quotient-based interregional input-output (IRIOLQ) framework - Malte Jahn (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2015)
The regionalization of national input-output tables is a major issue in regional science as corresponding regional data is often unavailable. In this paper, a framework is developed to estimate intra- and interregional input-output tables. The intraregional estimates are based on the wellaccepted FLQ method. The interregional estimates include gravity model-based estimates to account for geographical distances between the regions. The estimates are embedded in an interregional accounting framework which ensures consistency of regional values with the national aggregates. The framework is applied to the German economy of 2010. We are able to show the importance of taking into account interregional input-output relations in the derivation of (regional) demand multipliers.
Keywords: 330